Influence of the oxidizer on the formation and purification efficiency of acid gases produced during asphaltene gasification; Известия Томского политехнического университета [Известия ТПУ]. Инжиниринг георесурсов; Т. 333, № 4 - Ermolaev D. V. Denis Vasilievich (2022, 2022)
Заглавие с титульного листа